The predictors of entrepreneurial intention among undergraduate students / Rosliza Md Zani, Sarah Sabir Ahmad and Azfahanee Zakaria - Md Zani, Rosliza; Sabir Ahmad, Sarah; Zakaria, Azfahanee (2016)
Entrepreneurial education has become a concern in Malaysia. Knowing the importance of entrepreneurship and the urgency from the government, the universities in Malaysia have taken proactive actions to realise this education. This study aims to identify the predictors of entrepreneurial intentions among undergraduate students, considering curiosity, risk taking and creativity as the variables. The results found that risk taking and creativity have positive relationship with entrepreneurial intention. From the three variables tested, creativity is found to be the most dominant predictor of entrepreneurial intention. This study helps the management of higher institutions to educate the students on risk taking as well as creativity in order to make them successful entrepreneurs.